RURAL FARMER’S PREFERENCE FOR SEED ATTRIBUTES AND SUPPORT SERVICE FROM GRAIN TRADERS INFLUENCE THE ADOPTION OF IMPROVED VARIETIES IN MUBI REGION, ADAMAWA STATE, NIGERIA - Garandi, Danjuma Ijudigal; Bukar, Hyelnacha A.; Chukwu, Paulinus I.; Tanko, Hassan S.; Wesley, Phelimon; Dasin, Mohammed Saadu; Gabul, Peter (FUDMA Journal of Sciences, 2025)
This study examined the joint association of traders’ support services and seed attribute preferences on the adoption of improved sorghum, beans, and groundnut seed varieties in Mubi region. The study involved 961 farmers from major production districts of beans, sorghum and groundnuts. 315 bean, 317 sorghum, and 329 groundnut farmers from five (5) local government area (4 districts per crop) in Adamawa State, Nigeria. Data collection was conducted using a household survey via Survey CTO, and data analysis was analyzed using descriptive statistics, independent sample T test and Chi-square test. Results show that 89.2% credit on improved seed such as sorghum and groundnuts significantly enhances adoption when paired with key traits such as high yield (P Value 0.003), grain price (P Value 0.000), grain size (P. Value 0.000), drought tolerance (P Value 0.000), and pest-disease resistance (P Value 0.001). Market-based supports like market guarantee (63.6%) and market linkage (74.5%) also demonstrate strong joint effects with traits like attractive price (0.996), grain color (0.838), and maturity time (0.789), particularly in common beans and groundnuts. These findings highlight the critical role of integrated traders’ support and seed trait alignment in driving smallholder farmers’ seed adoption decisions.
Keywords: Improved seed adoption; Traders’ support service; Seed preference; Sorghum; Groundnuts; Beans; Mubi region